Penguatan Wawasan Moderasi Beragama Bagi Guru Madrasah Aliyah Berbasis Pesantren di Kabupaten Pangandaran - Heri Gunawan; Heri Hidayat (JRCE (Journal of Research on Community Engagement), 2025)
Indonesia is a country with extraordinary diversity (megadiversity) that includes ethnic groups, languages, and religions. This diversity is a gift from God that must be preserved in order to achieve national unity and integrity. As an effort to strengthen religious moderation, community service activities are carried out that focus on strengthening the understanding of religious moderation for Madrasah Aliyah teachers based in Islamic boarding schools. The community service program uses the Community-Based Participatory Research (CBPR) method, an approach that emphasizes empowerment, collaboration, and social change by involving the community as partners and agents of change. It was carried out in the Sabilil Muttaqin Islamic boarding school in Pangandaran Regency, involving 50 representative teachers from Islamic high schools based in Islamic boarding schools. This two-day workshop was also supported by the Pangandaran Regency Religious Harmony Forum and various related stakeholders. The results of the activity showed the importance of increasing teachers' knowledge of religious moderation to be integrated into the learning process. Participants were also expected to be able to develop an action plan to convey the values of religious moderation to students, creating a generation that is moderate, tolerant, and harmonious in diversity.